Front Cover: Gold(I)‐Catalysed Hydroarylation of Lactam‐Derived Enynes as an Entry to Tetrahydrobenzo[g]quinolines (Eur. J. Org. Chem. 6/2020). Issue 6 (30th January 2020) - Nejrotti, Stefano; Ghinato, Simone; Gini, Elena C.; Scarpi, Dina; Occhiato, Ernesto G.; Maranzana, Andrea; Prandi, Cristina
Abstract : The Front Cover shows a chemist picking a fruit from a tree with his golden glove. The fruit represents tetrahydrobenzo[ g ]quinolines, and the chemist is going to add it to other fruits he has already collected from the δ‐valerolactam tree. Indeed, the gold‐catalysed synthesis of tetrahydrobenzo[ g ]quinolines enlarges the palette of molecular scaffolds accessible in few steps from the same simple lactam precursor. The authors acknowledge Federico Sini for graphical support. More information can be found in the Full Paper by C. Prandi et al.